Analyzing X-ray tomographies of granular packings - Weis, Simon; Schröter, Matthias (Review of Scientific Instruments, 2017)
Starting from three-dimensional volume data of a granular packing, as, e.g., obtained by X-ray Computed Tomography, we discuss methods to first detect the individual particles in the sample and then analyze their properties. This analysis includes the pair correlation function, the volume and shape of the Voronoi cells, and the number and type of contacts formed between individual particles. We mainly focus on packings of monodisperse spheres, but we will also comment on other monoschematic particles such as ellipsoids and tetrahedra. This paper is accompanied by a package of free software containing all programs (including source code) and an example three-dimensional dataset which allows the reader to reproduce and modify all examples given.
EAM Import::2019-03-13

Structural similarity between dry and wet sphere packings - Weis, Simon; Schröder-Turk, Gerd; Schröter, Matthias (New Journal of Physics, 2019)
The mechanical properties of granular materials change significantly in the presence of a wetting liquid which creates capillary bridges between the particles. This results e.g. in a reduced value of the volume fraction when a packing is prepared with added liquid. Here we use x-ray tomography to demonstrate that this change in mechanical properties is not accompanied by structural differences between dry and wet sphere packings when compared at the same volume fraction. We characterize the structure of the packings by the average numbers of contacts of each sphere < Z > and the shape isotropy <beta(2,0)(0)> of the Voronoi cells of the particles. Additionally, we show that the number of liquid bridges per sphere < B > is approximately equal to < Z > + 2, independent of the volume fraction of the packing. These findings will be helpful in guiding the development of both particle-based models and continuum mechanical descriptions of wet granular matter.
CRIS-Team WoS Importer:2019-04-30